PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN JALAN DI KAWASAN TEMBAWANG DESA TANJUNG TENGANG KECAMATAN NANGA PINOH KABUPATEN MELAWI - Apriliansyah, Apriliansyah; Oramahi, H A; Idham, M (JURNAL HUTAN LESTARI, 2020)
Tanjung Tengang Village is one of the villages in Nanga Pinoh sub-district, Melawi Regency, which has a fairly extensive forest resource of around 1,257 Ha. The development in the Tembawang area of Tanjung Tengang Village can certainly affect the social and economic conditions of the community so that there is a perception that exists in the community. This study aims to determine people's perceptions of development in tembawang areas and the factors that influence them, age, knowledge and community education. This study uses a direct interview technique with a questionnaire tool, the determination of respondents was done by purposive sampling based on the Slovin formula of 85 respondents who live in the village of Tanjung Tengang. Characteristics of respondents are people who live in the village of Tanjung Tengang at least 5 years, physically and mentally healthy and at least 20 years old as head of the family. Data analysis consists of community perceptions of the development of tembawang areas and the relationship between age, knowledge and community education and community perceptions of the development of tembawang areas in Tanjung Tengang Village. Based on the calculation results of the three variables there is no relationship to public perception. The type of data consists of primary and secondary data and the research is conducted for one month in the field. The results showed the community's perception of the development of tembawang areas tended to be neutral, namely 64 respondents (75.29%), positive 13 respondents (15.29%) and negative as many as 8 respondents (9.41%). Characteristics of respondents in the village of Tanjung Tengang based on the age level are dominated by the adult age level, as many as 40 respondents (47.05%). Characteristics of respondents based on the level of knowledge are dominated by people with a medium level of knowledge as many as 65 respondents (76.47%) and for the characteristics of respondents based on the level of education are dominated by respondents with a high education level of 43 respondents (50.58%). Keywords: community perception, tembawang, road construction, melawi district